FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN KANKER SERVIKS DI PUSKESMAS KARANGANYAR - Yuniar, Isma; -, saryono; Rohyani, Fitri (LPPM STIKES MUHAMMADIYAH GOMBONG, 2009)
Cervix cancer is a cancer that is located in the uterus neck and the second most killer cancer after breast cancer that occurs in women around the world. Major risk factor for this cancer is infection by Human Papilloma Virus (HPV) to cervix that is transmitted sexually. The objective of the research was to find out the dominant factors that influence cervix cancer occurrence in Karanganyar Community Health Center. The method used in the research was analytical method with cross sectional approach. The samples were taken by using the purposive sampling. There were 70 respondents taken as the research samples. The analysis used chi square and logistic regression tests. Chi square test results showed that X2 factor of age at first time did sex = 11.667 (p = 0.001); X2 factor of the often of changing sex partners = 0.159 (p = 0.690); X2 factor of sexually transmitted disease history = - ; X2 of contraception factor = 6,357 (p = 0.012); X2 of parity factor = 0.915 (p = 0.317); X2 = smoking factors -. The results of research found that the factors that influenced the incidence of cancer were age at first time did sex and contraception factors. It can be concluded that there were correlation between age at first time did sex, and contraception factors with the occurrence of cervix cancer in Karanganyar Community Health Center. The most dominant factor that influences the occurrence of cervix cancer in Karanganyar Community Health Center is age at first tie did sex. Keywords: dominant factor, cancer cervix